Alexithymia explains increased empathic personal distress in individuals with and without eating disorders. Issue 7 (July 2019) - Brewer, Rebecca; Cook, Richard; Cardi, Valentina; Treasure, Janet; Catmur, Caroline; Bird, Geoffrey
It is often assumed that empathy impairments are common in individuals with eating disorders (EDs), but empirical work has been limited and produced mixed results, making the clinical features and treatment needs of this population difficult to determine. Alexithymia, characterised by difficulties identifying and describing one's own emotions, frequently co-occurs with EDs and is associated with atypical recognition of, and empathy for, others' emotions. This study used an existing empathy for pain paradigm to determine whether atypical empathy in EDs stems from co-occurring alexithymia, rather than EDs per se. Empathy (specifically personal distress in response to others' pain) was assessed in individuals with EDs ( N = 21) and an alexithymia-matched control group ( N = 22). Participants were simultaneously members of a high alexithymia ( N = 16) or low alexithymia ( N = 27) group, allowing the independent contributions of alexithymia and EDs to be determined. Participants judged the laterality of hands and feet in painful and non-painful situations, and the degree of empathic interference on response times was measured. Results indicated that observation of painful stimuli affected task performance in those with high levels of alexithymia more than those with low levels, but no effect of ED diagnosis was observed. These findings suggest that co-occurring alexithymia explains increased empathic personal distress in ED populations. Atypical empathy may therefore not be a core feature of EDs, and interventions aimed at improving empathy-related social functioning may only be necessary for patients who also have alexithymia. These findings emphasise the importance of determining the influence of co-occurring alexithymia when assessing empathy in clinical populations.